Genetic diversity and economic development: Assessing the key findings in Ashraf and Galor (2013) - Raymond Caraher; Michael Ash (University of Massachusetts, Department of Economics, 2018)
We replicate Ashraf and Galor (2013) and find that its conclusions concerning the association between human genetic diversity and economic development depend substantially on coding errors and sample selection. We correct the coding errors and add or update data on genetic diversity and population density from high-quality sources. We find little support for the hypothesis that variation in genetic diversity among subpopulations has a systematic relationship with economic development.
Keywords: N10; N30; N50; O10; O50; Z10; 330; genetics; development